A Unique Case of Bilateral Thalamic High-Grade Glioma in a Pediatric Patient with LI-Fraumeni Syndrome: Case Presentation and Review of the Literature - Raffaella Messina; Gerardo Cazzato; Teresa Perillo; Vita Stagno; Valeria Blè; Mariachiara Resta; Francesco De Leonardis; Nicola Santoro; Francesco Signorelli; Giuseppe Ingravallo (MDPI AG, 2021)
Li-Fraumeni syndrome (LFS) is a rare high-penetrance and autosomal-dominant pathological condition caused by the germline mutation of the TP53 gene, predisposing to the development of tumors from pediatric age. We conducted a qualitative systematic review following the ENTREQ (Enhancing Transparency in Reporting the Synthesis of Qualitative Research) framework. A search was made in MEDLINE/Pubmed and MeSH Database using the terms "Li-Fraumeni" AND "pediatric high-grade glioma (HGG)", identifying six cases of HGGs in pediatric patients with LFS. We added a further case with peculiar features such as no familiar history of LFS, association of embryonal rhabdomyosarcoma and bithalamic HGG, whose immunohistochemical profile was accurately defined by Next Generation Sequencing. Knowledge synthesis and case analysis grounded the discussion about challenges in the management of this pathology in pediatric age.